2021
DOI: 10.3390/cancers13071566
|View full text |Cite
|
Sign up to set email alerts
|

UGT1A1 Guided Cancer Therapy: Review of the Evidence and Considerations for Clinical Implementation

Abstract: Multi-gene assays often include UGT1A1 and, in certain instances, may report associated toxicity risks for irinotecan, belinostat, pazopanib, and nilotinib. However, guidance for incorporating UGT1A1 results into therapeutic decision-making is mostly lacking for these anticancer drugs. We summarized meta-analyses, genome-wide association studies, clinical trials, drug labels, and guidelines relating to the impact of UGT1A1 polymorphisms on irinotecan, belinostat, pazopanib, or nilotinib toxicities. For irinote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 102 publications
1
32
0
Order By: Relevance
“…EMs were found in 46.1% of patients. Our data are generally in accordance with those reported by the CPIC guidelines, which showed that the prevalence of PMs, IMs, and EMs is 8%, 42%, and 50%, respectively, in East Asians [22].…”
Section: Discussionsupporting
confidence: 92%
“…EMs were found in 46.1% of patients. Our data are generally in accordance with those reported by the CPIC guidelines, which showed that the prevalence of PMs, IMs, and EMs is 8%, 42%, and 50%, respectively, in East Asians [22].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the expected American/European population frequency, UGT1A1 variants were common (157/291, 54%). UGT1A1 genotype status impacts irinotecan metabolism, often indicated for front-line treatment of gastrointestinal malignancies [ 14 , 15 ]. Over half (45/86, 52.3%) of the patients who could potentially receive irinotecan as a component of an NCCN “preferred” regimen harbored a UGT1A1 variant.…”
Section: Resultsmentioning
confidence: 99%
“…Though variant-associated toxicity is established for TPMT [ 17 ], UGT1A1 [ 15 ], and DPYD [ 16 ] intermediate and poor metabolizers, testing is not routinely performed and clinical management guidelines for dosing are inconsistent. This is likely related to logistical barriers, lack of clinical utility, and cost associated with routine pharmacogenomic screening [ 7 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar mechanism has been also observed for pazopanib, a TKI for patients with advanced renal cell carcinoma. UGT1A1*28 patients should be monitored for higher adverse reaction risk(26). The same drug treatment can promote deregulation of liver enzymes levels in patients carrying the HLB*5701 variant and should carefully followed-up…”
mentioning
confidence: 99%